Nanoparticle-mediated drug delivery for treating melanoma. (August 2015) - Mundra, Vaibhav; Li, Wei; Mahato, Ram I
Melanoma originated from melanocytes is the most aggressive type of skin cancer with limited treatment options. New targeted therapeutic options with the discovery of BRAF and MEK inhibitors have shown significant survival benefits. Despite the recent progress, development of chemoresistance and systemic toxicity remains a challenge for treating metastatic melanoma. While the response from the first line of treatment against melanoma using dacarbazine remains only 5–10%, the prolonged use of targeted therapy against mutated oncogene BRAF develops chemoresistance. In this review, we will discuss the nanoparticle-based strategies for encapsulation and conjugation of drugs to the polymer for maximizing their tumor distribution through enhanced permeability and retention effect. We will also highlight photodynamic therapy and design of melanoma-targeted nanoparticles.